Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.stem.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Human Hippocampal Neurogenesis Persists in Aged Adults and Alzheimer’s Disease Patients

Abstract: Whether hippocampal neurogenesis persists throughout life in the human brain is not fully resolved. Here, we demonstrate that hippocampal neurogenesis is persistent through the tenth decade of life and is detectable in patients with mild cognitive impairments and Alzheimer's disease. In a cohort of 18 participants with a mean age of 90.6 years, Nestin + Sox2 + neural progenitor cells (NPCs) and DCX + neuroblasts and immature neurons were detected, but their numbers greatly varied between participants. Nestin +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
422
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 448 publications
(474 citation statements)
references
References 35 publications
22
422
1
1
Order By: Relevance
“…Moreno-Jiménez et al, 2019 using tightly controlled conditions and state-of-the-art tissue processing methods, identified thousands of immature neurons, exhibiting variable degrees of maturation along differentiation stages, in DG of the neurologically healthy human subjects up to the ninth decade of life. They additionally found that continued neurogenesis was reduced in DG of Alzheimer's patients (8). Tobin et al, 2019 found AHN to persistent through the tenth decade of life and being detectable in patients with mild cognitive impairments and Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreno-Jiménez et al, 2019 using tightly controlled conditions and state-of-the-art tissue processing methods, identified thousands of immature neurons, exhibiting variable degrees of maturation along differentiation stages, in DG of the neurologically healthy human subjects up to the ninth decade of life. They additionally found that continued neurogenesis was reduced in DG of Alzheimer's patients (8). Tobin et al, 2019 found AHN to persistent through the tenth decade of life and being detectable in patients with mild cognitive impairments and Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 98%
“…Studies with contrasting evidence have emerged since then which ranged from absolute denial (3)(4)(5) to approval for the persistence of AHN even in old individuals (6)(7)(8). In adult mammals (including human) neurogenesis is thought to persist in the subgranular zone (SGZ) of the dentate gyrus (DG) region of the hippocampus (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, neurogenesis confers resilience to chronic stress by inhibiting the activity of mature granule cells in the ventral DG . Notably, hippocampal neurogenesis in the DG also persists into old age . These findings suggest that approach‐oriented coping strategies may suppress atrophy and promote neurogenesis in the hippocampi of elderly persons who maintain their ADL and cognitive function.…”
Section: Discussionmentioning
confidence: 93%
“…The hippocampus retains the ability to produce new neurons in adulthood in a variety of species including humans (Kempermann et al, 2018;Moreno-Jiménez et al, 2019;Tobin et al, 2019). Adult hippocampal neurogenesis is reduced by chronic stress, promotes stress resilience, and is implicated in affective function and hypothalamic-pituitary-adrenal (HPA) axis regulation (Anacker et al, 2018;Schoenfeld and Gould, 2012;Surget et al, 2011), although most of this evidence is derived from male rodents.…”
Section: Introductionmentioning
confidence: 99%